Incidence, Nature, and Etiology of Metabolic Alkalosis in Dogs and Cats. (10th June 2013) - Ha, Y.‐S.; Hopper, K.; Epstein, S.E.
<x xml:space="preserve">Abstract</x> Background The incidence and causes of metabolic alkalosis in dogs and cats have not been fully investigated. Objectives To describe the incidence, nature, and etiology of metabolic alkalosis in dogs and cats undergoing blood gas analysis at a veterinary teaching hospital. Animals Dogs and cats at a veterinary medical teaching hospital. Methods Acid–base and electrolyte results for dogs and cats measured during a 13‐month period were retrospectively collected from a computer database. Only the first measured (venous or arterial) blood gas analyzed in a single hospitalization period was included. Animals with a base excess above the reference range for the species were included. Results A total of 1, 805 dogs and cats were included. Of these, 349 (19%) were identified as having an increased standardized base excess, 319 dogs and 30 cats. The mixed acid–base disorder of metabolic alkalosis with respiratory acidosis was the most common abnormality identified in both dogs and cats. Hypokalemia and hypochloremia were more common in animals with metabolic alkalosis compared to animals without metabolic alkalosis. The 4 most commonly identified underlying diseases were respiratory disease, gastrointestinal tract obstruction, furosemide administration, and renal disease. Conclusions and Clinical Importance Metabolic alkalosis was less common than metabolic acidosis in the same population of animals. Evidence of contraction alkalosis was present in many patients in this study. Hypokalemia and hypochloremia were more frequent in patients with metabolic alkalosis and suggest the importance of evaluation of acid–base status in conjunction with serum electrolyte concentrations.